2022
DOI: 10.1093/eurjcn/zvac100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of six frailty instruments in adults with heart failure: a prospective cohort pilot study

Abstract: Aim To compare the frailty prevalence and predictive performance of six frailty instruments in adults with heart failure and determine feasibility of study methods. Methods and Results Prospective cohort pilot study. Adults aged 18 years or older with a confirmed diagnosis of heart failure in Sydney, New South Wales, Australia. The Frailty Phenotype; the Survey of Health, Ageing and Retirement in Europe Frailty Instrument (SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Of the included studies, 13 studies were considered of having a high risk of bias [ 7 , 31 , 32 , 39 , 41 , 43 , 46 , 52 , 53 , 60 , 61 , 63 , 64 ], 16 as moderate risk of bias [ 18 , 29 , 33 , 36 , 37 , 42 , 44 , 45 , 48 50 , 55 , 56 , 58 , 59 , 62 ], and 12 studies had a low risk [ 28 , 30 , 34 , 35 , 38 , 40 , 47 , 51 , 54 , 57 , 65 , 66 ] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 13 studies were considered of having a high risk of bias [ 7 , 31 , 32 , 39 , 41 , 43 , 46 , 52 , 53 , 60 , 61 , 63 , 64 ], 16 as moderate risk of bias [ 18 , 29 , 33 , 36 , 37 , 42 , 44 , 45 , 48 50 , 55 , 56 , 58 , 59 , 62 ], and 12 studies had a low risk [ 28 , 30 , 34 , 35 , 38 , 40 , 47 , 51 , 54 , 57 , 65 , 66 ] (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies assessed the prevalence of polypharmacy [20][21][22][23][24][25][26] and six studies assessed the number of medications [14][15][16][17][18][19] administered by patients with HF and frailty vs. without frailty. Detailed characteristics of the included studies are presented in Tables 1 and 2.…”
Section: Descriptive Resultsmentioning
confidence: 99%
“…Of the final 72 studies identified as eligible for inclusion in our study, 58 articles included only data related to specific medications rather than polypharmacy rates and total number of medications, while one study defined frailty as short physical performance battery score below 6. Overall, 13 studies were included in this systematic review and meta-analysis (Figure 1) [14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult participants of the FRAilty MEasurement in Heart Failure (FRAME-HF) study, SHARE-FI was able to discriminate between inpatients and outpatients 44 . In a small pilot Australian study with 131 adults with HF (mean age 54), SHARE-FI seemed to have, together with the Deficits Accumulation Index (DAI), the highest C-statistic value (0.73) for the prediction of rehospitalisation and/or mortality at 12 months, followed by the original Frailty Phenotype (FP) (0.72), and the St Vincent's Frailty instrument (0.71) 45 ; however, results for the multiple logistic regression models were not statistically significant. A Polish study proposed a novel model to predict frailty (based on SHARE-FI) in HF patients using the following five variables: age >50 years, systolic blood pressure (SBP) on admission <110 mmHg, total cholesterol <4.85 mmol/L, bilirubin ≥15.5 mmol/L, and ALT ≤34 U/L 46 .…”
Section: Other Diseasesmentioning
confidence: 99%